Dedifferentiated Liposarcoma With Epithelioid/Epithelial Features. (November 2017) - Makise, Naohiro; Yoshida, Akihiko; Komiyama, Motokiyo; Nakatani, Fumihiko; Yonemori, Kan; Kawai, Akira; Fukayama, Masashi; Hiraoka, Nobuyoshi
Abstract : Dedifferentiated liposarcoma (DDLPS) demonstrates a variety of growth patterns, and their histologic resemblance to other spindle cell mesenchymal tumors has been widely recognized. However, epithelioid morphology in DDLPS has only rarely been documented. Here, we report 6 cases of DDLPS with striking epithelioid/epithelial features. The patients were 5 men and 1 woman with a median age of 61 years. All tumors were located in the internal trunk. During follow-up of 1 to 41 months, local recurrence, distant metastases, and tumor-related death occurred in 4, 2, and 4 patients, respectively. Beside well-differentiated liposarcoma component and conventional high-grade spindle cell morphology, all tumors focally exhibited growth comprising small or large epithelioid cells in diffuse or sheet-like proliferation. Rhabdoid cells were present in 2 cases. All 5 tumors tested harbored MDM2 amplification. Cytokeratin and/or epithelial membrane antigen were at least focally positive in all 5 tumors tested. One case contained a small focus of novel heterologous epithelial differentiation with acinar structures, wherein cytokeratin, MOC31, and claudin-4 were diffusely expressed and H3K27me3 expression was lost. DDLPS with epithelioid/epithelial features may lead to misdiagnosis of carcinoma or mesothelioma, and their diagnosis should be based on correlation with clinicopathologic and molecular findings. The epithelioid morphology in DDLPS may suggest an aggressive behavior based on this small series. In addition, we document 2 cases of MDM2 -amplified undifferentiated neoplasm with epithelioid features in the internal trunk that lacked association with well-differentiated liposarcoma histology and showed rapid clinical course. Whether these latter tumors belong to DDLPS with epithelioid features requires further study.